Democratic Republic of Sao Tome and Principe : First Review Under the Extended Credit Facility Arrangement. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2013)
This paper discusses the Democratic Republic of Sao Tome and Principe's First Review under the Extended Credit Facility Arrangement. The economy remains vulnerable to external and domestic shocks. Growth decelerated to 4 percent in 2012, reflecting persistent global uncertainties, particularly in Europe, which contributed to a slowdown in foreign direct investment, and in the execution of the foreign-financed public investment program. Commercial banks profitability and capital-to-risk weighted assets ratio declined in 2012, reflecting more challenging lending conditions. The central bank continues to strengthen its banking supervision function through on-site inspections and enforcement of banking regulation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet